KEPEMILIKAN INSTITUSIONAL, KARAKTERISTIK EKSEKUTIF, FIX ASSETS INTENSITY, DAN PENGHINDARAN PAJAK: SUBSEKTOR TRANSPORTASI DAN LOGISTIK - Rizki, Marsi Fella; Silaen, Rudi Sabam (Universitas Teknokrat Indonesia, 2024)
This study aims to prove the effect of institutional ownership, management characteristics, and fix asset intensity on tax avoidance in transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) in 2019 to 2023. There are 30 transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) in 2023. Meanwhile, the sample of this study amounted to 12 samples with 60 observations selected using the purposive sampling method. . Based on the test results, it proves that institutional ownership has no effect on tax avoidance, leadership characteristics have a negative effect on tax avoidance, and fix asset intensity has no effect on tax avoidance. Furthermore, institutional ownership, executive characteristics, and fix asset intensity simultaneously have no effect on tax avoidance.